Crime and immigration - Brian Bell (IZA World of Labor, 2019)
Immigration is one of the most important policy debates in Western countries. However, one aspect of the debate is often mischaracterized by accusations that higher levels of immigration lead to higher levels of crime. The evidence, based on empirical studies of many countries, indicates that there is no simple link between immigration and crime, but legalizing the status of immigrants has beneficial effects on crime rates. Crucially, the evidence points to substantial differences in the impact on property crime, depending on the labor market opportunities of immigrant groups.
Keywords: J15; J61; K42; 330; migration; immigration; crime; employment